Construção de uma matriz de referência para futura elaboração de um indicador de literacia midiática brasileiro - Moraes , Tamara Hashimoto Natale de (2024)
The skill to critically access content is crucial for social life, consumer decision-making or civic engagement. With the growing volume of information received every day and the advance of Information and Communication Technologies (ICTs), consumers of information no longer play a passive role. They consume, produce, share, engage, and create content, and consequently they form relationships in the digital world that are not conditioned by physical distance, rather by a person’s lenses and biases. The reproduction of unbalanced content and misinformation may lead to a variety of problems, and the evaluation and measurement of this diffusion is a major challenge. Since problems such as the creation of different behavioral profiles between the physical world and the virtual world, the massive growth of false information that spreads so quickly that it can no longer be fought, to issues of inclusion, equity and human rights, lead media literacy as an essential pillar in contemporary society, providing social, emotional, and productive insertion of citizens. Media education prepares people for the new times, teaching essential skills and competencies for critical integration with modern media. It also acts as a fundamental axis for the exercise of democracy. The objective of this study was twofold: (1) to understand the key concepts and contexts surrounding the topic of media literacy, and (2) to develop a reference framework for the future creation of a media education KPI for Brazil. Employing the Design Science Research (DSR) methodology, we crafted a comprehensive reference framework that amalgamates previously advocated theories and concepts, thereby providing a cohesive artifact for application in future studies.